Dietary Tribulus Terrestris as a functional food combined with blood flow restriction to enhance the jump performance of basketball athletes: a randomized crossover study - Kong, Junhao; Li, Jinda; Xu, Mingchen; Liu, Tao; Xie, Zhiyu; Li, Tianhe; Liang, Yapu (Frontiers in Nutrition, 2025)
IntroductionTribulus terrestris (TT), a food-derived functional ingredient, may influence neuromuscular function via its bioactive compounds, but its acute effects on BFR-induced PAP and performance remain unknown. This study examined its short-term effects on neuromuscular performance after BFR-primed PAP in elite male basketball athletes (n = 20).MethodsParticipants completed two sessions involving BFR-augmented plyometric protocols with either TT or placebo. CMJ performance was assessed at 0, 4-, 8-, 12-, and 16-min post-activation, measuring jump height (H(v)), peak/relative peak power (PP/RPP), maximum/relative force (MCF/MRF), peak rate of force development (PRFD), and modified reactive strength index (RSImod). Paired-sample t-tests (p < 0.05) were used for analysis.ResultsIn the placebo condition, H(v) increased at 4 and 8 min (p < 0.05), with PP and RPP peaking at 8 min (p < 0.05). TT supplementation enhanced early-phase force dynamics, elevating MCF (p = 0.057, 0 min; p < 0.01, 4 min) and PRFD (p = 0.002, 4 min), but attenuated H(v) (p < 0.001, 16 min), PP (p < 0.001), and RPP (p < 0.001) during later phases. Between-group comparisons revealed superior power metrics in the placebo group at 8–16 min (H(v): p = 0.001–0.017; RPP: p = 0.004–0.001), while TT transiently improved PRFD (p = 0.049, 0 min) and RSImod (p = 0.017, 4 min; p = 0.019, 16 min).ConclusionAcute intake of TT modulates early-phase force responses but may impair sustained power output during PAP. Targeted timing and delivery formats should be considered in future food-first performance strategies.